Inhibition by Marine Algae of Chikungunya Virus Isolated From Patients in a Recent Disease Outbreak in Rio de Janeiro - Cirne-Santos, Claudio Cesar; Barros, Caroline de Souza; Nogueira, Caio Cesar Richter; Azevedo, Renata Campos; Yamamoto, Kristie Aimi; Meira, Guilherme Louzada Silva; Vasconcelos, Zilton Farias Meira de; Ratcliffe, Norman Arthur; Teixeira, Valéria Laneuville; Schmidt-Chanasit, Jonas; Ferreira, Davis Fernandes; Paixão, Izabel Christina Nunes de Palmer (Frontiers in Microbiology, 2019)
Chikungunya virus (CHIKV) infection is one of the most challenging re-emergent diseases caused by a virus and with no specific anti-viral treatment it has now become a major public health concern. In this investigation, 25 blood samples were collected from patients with characteristic CHIKV symptoms and submitted to a virus isolation protocol, which detected 3 CHIKV isolates. These samples were evaluated by sequencing for the characterization of the strains and any homology to viruses circulating in Brazil during a recent outbreak. These viruses were used for the development of antiviral assays. Subsequently, the inhibitory effects of seaweed extracts on CHIKV replication were studied. The marine species of algae tested were Bryothamnion triquetrum, Caulerpa racemosa, Laurencia dendroidea, Osmundaria obtusiloba, Ulva fasciata and, Kappaphycus alvarezii, all of which are found in different countries including Brazil. The results revealed high levels of CHIKV inhibition including extracts of O. obtusiloba with inhibition values of 1.25µg / mL and a selectivity index of 420. Viral inhibition was dependent upon the time of addition of extract of O. obtusiloba to the infected cells with the optimal inhibition occurring up to 16 h after infection. Neuron evaluations with O. obtusiloba were performed and demonstrated low toxicity and in infected neurons we observed high inhibitory activity in a dose-dependent manner. These results indicate that the algal extracts may be promising novel candidates for the development of therapeutic agents against CHIKV infections.